2018
DOI: 10.1063/1.5034071
|View full text |Cite
|
Sign up to set email alerts
|

Application of plasma for efficient H2 production: A realism of copper electrode in single dielectric barrier discharge reactor

Abstract: Effective transformation of moisture into hydrogen in argon containing 100% relative humidity employing dielectric barrier discharge cold plasma is reported. The coaxial reactor with a common outer Pyrex tube having an inner diameter of 14 mm accompanied by a central electrode combination is employed for H2 generation through water splitting. Three different central electrodes such as Pyrex (double dielectric surfaces), copper (Cu), and stainless steel (SS) [single dielectric (SD) surface] are used separately,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…So, it may be understood that the residue also contains untreated methanol as a major part which has not been degraded. As per the recent available report, Dey et al reported H 2 production using DBD plasma technique with an inbuilt Cu electrode [79]. El-Shafie et al studied the hydrogen generation from water vapour decomposition with application of plasma as energy source [80,81].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…So, it may be understood that the residue also contains untreated methanol as a major part which has not been degraded. As per the recent available report, Dey et al reported H 2 production using DBD plasma technique with an inbuilt Cu electrode [79]. El-Shafie et al studied the hydrogen generation from water vapour decomposition with application of plasma as energy source [80,81].…”
Section: Resultsmentioning
confidence: 99%
“…As per the recent available report, Dey et al. reported H 2 production using DBD plasma technique with an inbuilt Cu electrode [ 79 ]. El-Shafie et al.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that the H 2 and H 2 O 2 were generated in Ar‐moisture cold plasma . The present study was explored to utilize these products (especially H 2 ) in Ar–Bz cold plasma using reactor R2 for Bz transformation employing System A conditions (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The gaseous sample delivery system was 20 ± 5 ml/min, which was controlled with a suitable mass flow controller (MFC). This type of arrangement is aimed under the study for chemical reduction/transformation of Bz to a greater extent, expecting significant contribution of in situ H 2 , generated in moisture‐containing Ar systems . The various combinations of experiment sets employed under the study are listed in Table .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation